Pain Management in Acute Fracture Care: Current Concept Review - Swarup, Ishaan; Pandya, Nirav (Journal of the Pediatric Orthopaedic Society of North America, 2021)
The management of pediatric and adolescent pain continues to evolve. Pain, as in the adult population, is a complex process modulated by both physiologic and psychological factors. It is essential for the orthopedic clinician who manages pain in the acute setting to not only understand the medical aspects of pain control, but also the larger context in which the injury is taking place. The opioid crisis has changed the manner in which pain management is delivered, and an understanding of pediatric physiology is critical for delivering analgesia. This is particularly important in the setting of acute fracture management. Utilization of anti-inflammatory medications, diversion techniques, and regional anesthesia are integral to management in the emergency room, pre-operatively, intra-operatively, and post-operatively. A multi-faceted, holistic approach is essential to achieve successful clinical outcomes.